2013
DOI: 10.1051/meca/2013076
|View full text |Cite
|
Sign up to set email alerts
|

Free vibration analysis of truncated conical fiber metal laminate (FML) shells

Abstract: In this paper, an analytical solution is developed for free vibration analysis of conical fiber metal shells. In order to find constitutive relations, the assumptions of thins hells are used and the governing equations are based on Love's theory. The Galerkin method is employed to solve the governing equations in which beam functions are used to approximate the mode shapes. Using beam functions enables us to assess the effects of different boundary conditions on the frequency response of the shells. Numerical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…It was stated that the natural frequency increased by raising the height-to-width ratio. For instance, Ghasemi et al [38] investigated 7 plies θ = 0 • , 90 • Hinged-hinged FML beam [35] geometrical parameters and embedded aluminum plies with different layers on the natural frequency of the truncated conical FML shell with various boundary conditions. It was found that increasing the number of embedding aluminum increased the frequency parameter.…”
Section: Micromechanical Approachmentioning
confidence: 99%
“…It was stated that the natural frequency increased by raising the height-to-width ratio. For instance, Ghasemi et al [38] investigated 7 plies θ = 0 • , 90 • Hinged-hinged FML beam [35] geometrical parameters and embedded aluminum plies with different layers on the natural frequency of the truncated conical FML shell with various boundary conditions. It was found that increasing the number of embedding aluminum increased the frequency parameter.…”
Section: Micromechanical Approachmentioning
confidence: 99%
“…The vibration equation for the cylindrical or shell-shaped element can be obtained using Kirchoff's theory or shear deformation theories. These equations can be solved numerically by the Galerkin method, and dynamic analysis can be performed (Ghasemi et al, 2013a;Khalili et al, 2010;Malekzadeh et al, 2010). It has been determined that the natural frequencies have the maximum values when the aluminum layer is located at the bottom and top of the structure in the clamped-free boundary condition.…”
Section: Free Vibration Analysis Of Fml Composite Platesmentioning
confidence: 99%
“…The vibration equation for the cylindrical or shell-shaped element can be obtained using Kirchoff's theory or shear deformation theories. These equations can be solved numerically by the Galerkin method, and dynamic analysis can be performed (Ghasemi et al. , 2013a; Khalili et al.…”
Section: Introductionmentioning
confidence: 99%